Informational letter about the Association of Scientists for Atomic Education - Association of Scientists for Atomic Education (1947)
Letter to the members of the Association of Oak Ridge Engineers and Scientists (AORES) from the newly formed Association of Scientists for Atomic Education (ASAE). ASAE was founded on December 19, 1946. It was created for scientists and engineers interested in educating others on the social implications of science.
Keywords: Association of Scientists for Atomic Education; Association of Oak Ridge Engineers and Scientists